SAT0503 Is There a Benefit in using Morphological and Perfusion-Based MRI Measurements in the Follow-Up of Patients with Rheumatoid Arthritis Treated with Anti-IL-6 Antibody? – a Comparison with Clinical Scores and Serologic Data. (23rd January 2014) - Horger, M.; Grosse, U.; Koetter, I.; Claussen, C. D.; Henes, J.
Abstract : Background: In the last years the development of new anti-rheumatic drugs based on the current state of knowledge with respect to pathogenic mechanisms involved in RA and especially in RA-related bone destruction was pursued. At this point, one therapeutic target represents IL-6 which is presumed to aggravate local inflammatory reaction by augmenting inflammatory cell infiltration. Consequently, the inhibition of IL-6 has proven beneficial for RA patients as documented by recent data. IL-6 inhibition causes early and sustained decrease in acute-phase response markers (ESR and serum CRP), limiting the sensitivity of such serologic markers for assessment of the degree of activity of the underlying autoimmune process responsible for RA. Due to this limitation, clinical, serology-independent disease activity scores (CDAI) were developed for more accurate evaluation of the course of the disease during treatment with biologics, particularly, anti-IL-6R agents. Assuming that the autoimmune process might evolve on a subclinical level, we have decided to add a perfusion-based additional functional MRI tool to the already established morphologic MR imaging information in order to more confidently objectify all disease-related abnormalities of articular or tendon synovium and bone marrow. Objectives: Evaluation of response to anti-IL-6 receptor antibody Tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) 4, 12 and 24 weeks after treatment initiation using morphology- and perfusion-based MRI parameters in comparison to serologic biomarkers (C-reactive protein [CRP]) and clinical assessment scores (DAS-28-ESR and CDAI). Methods: Nine patients (2 men, 7 women; 48.0 ± 12.6 years) with longstanding active RA and prior ineffective treatments (including anti-TNF agents) were initially enrolled. MRI protocol included T2w SE, T1w and a fat-suppressed dynamic T1w sequence. Data evaluation followed modified OMERACT-RAMRIS recommendations. Additionally, DCE-MRI parameter maps (k-trans, Ve and Vp), noise corrected relative enhancement (RE) at 52 seconds and the rate of early enhancement (REE) were calculated. Results: DAS-28-ESR decreased significantly at 4, 12 and 24 weeks post-treatment whereas the decrease of CDAI reached significance solely at week 12. The strong decrease of ESR was statistical significant after week 12 and 24. None of the morphological and functional MRI parameters presented significant changes at 4 and 12 weeks while synovial volume, RE and REE significantly decreased at week 24. Although statistically not significant, semi-quantitative parameters showed a stronger decrease of MRI parameters in the responder-group after 12 weeks of treatment with TCZ. Conclusions: Semi-quantitative perfusion-derived MRI parameters might detect response of RA to TCZ therapy more accurately in comparison to morphology-based MRI scores (RAMRIS) except for synovial volume measurements. Clinical scores (DAS-28-ESR) and laboratory measurements (ESR) showed a significant decrease already after 4 and 12 weeks, respectively, but this change was similar among responders and non-responders. Disclosure of Interest: None Declared